2006
DOI: 10.1080/09553000600840930
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of stable chromosomal aberrations in gamma-ray irradiated non-human primates

Abstract: We confirmed the long-term stability of translocations and found that it seems to depend on the type of the translocation recorded. Overall translocations were stable for up to 31 months regardless of dose, but two-way translocations were more stable than those that were non-reciprocal, especially in stable cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
(34 reference statements)
1
4
0
1
Order By: Relevance
“…Non-human primate model systems of study also exhibit radiation-induced depletion. Tn particular, Macaca fascicularis can exhibit a 70% depletion of total lymphocytes 24 h after 2 and 4 Gy irradiation (29). These findings harmonize with depletion effects seen also in human subjects of study.…”
Section: Discussionsupporting
confidence: 79%
“…Non-human primate model systems of study also exhibit radiation-induced depletion. Tn particular, Macaca fascicularis can exhibit a 70% depletion of total lymphocytes 24 h after 2 and 4 Gy irradiation (29). These findings harmonize with depletion effects seen also in human subjects of study.…”
Section: Discussionsupporting
confidence: 79%
“…These results are encouraging for the utility of the MNi biomarker in a partial body, long-term animal model. Previously, Gregoire et al reported elevated translocation and dicentric chromosome frequencies in blood samples from total body gamma ray irradiated NHPs up to 31 months after irradiation [ 50 ] and Thierens et al were able to derive dose estimates from dicentrics chromosomes and micronucleus frequencies 6 months after an accidental exposure of a radiological worker [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…1). Même si quelques études ont montré une décroissance du taux de translocations avec le temps (Bauchinger et al, 2001 ;Lindholm et Edwards, 2004 ;Sorokine-Durm et al, 2000a ;Tucker, 2008), la stabilité des translocations est incontestablement meilleure que celle des dicentriques Grégoire et al, 2006 ;Lindholm et Edwards, 2004 ;Pala et al, 2001 ;Tawn et al, 2006 ;Tucker, 2008). L'étude de patients traités par radiothérapie durant des dizaines d'années pour spondylarthrite ankylosante, suggère que les translocations semblent persister plusieurs années après l'exposition (Buckton et al, 1962).…”
Section: Introductionunclassified